HISTOPATHOLOGICAL STRUCTURE OF WHITE RATS LIVER AFTER GIVING ANT NEST EXTRACT DUE TO INDUCED PARACETAMOL TOXIC DOSE - Merdana, I Made; Kardena, I Made; Budiasa, Ketut; Gunawan, I Made Dodi (Buletin Veteriner Udayana, 2019)
This study aim was to determine the influence ant nest plant extract (Myrmecodia pendans) on histopathological changeof white rat liver (Rattus novergicus) due to induced with paracetamol toxic dose. This study used 24 male white rats, divided into four groups, negative control group (P0) given placebo, positive control group (P1) given paracetamol dose 250 mg / kg bw for 10 days, P2 given ant nest extract 250 mg / kg bw and paracetamol dose 250 mg / kg bw for 10 days, P3 given ants nest extract 250 mg / kg bw for seven days, then continued by giving paracetamol and ants nest extract with dose 250 mg / kg bw for ten days. After the treatment done, all the rats were dinecropsed. Liver organs were taken and processed for making histopathology preparations. Parameters examined included hemorrhage, congestion, degeneration and necrosis. The data obtained were analyzed statistically by using Kruskal Wallis test followed by Mann Whitney test. Mann Whitney test results for all categories of histopathologic changes in  hemorrhagic, congestion, degeneration, and necrosis between negative control group (P0) and positive control group (P1) were significantly different (P <0.05), between negative control (P0) with P2 and P3 there was no significant difference (P> 0,05). Afterward, between the positive control (P1) and P2 with P3 there was a significant difference (P <0.05). I can be concludedthat the administration of paracetamol dose 250 mg/kg bw for 10 days affects the histopathologic changes of white rat liver. The administration of ant nest plant extracts can reduce the side effects of toxic doses of paracetamol.